A public finance analysis of multiple reserve requirements - Marco Espinosa-Vega; Steven Russell (Federal Reserve Bank of Atlanta, 1999)
This paper analyzes multiple reserve requirements of the type that have been imposed by a number of developing countries. We show that previous theoretical work on this topic has not succeeded in providing a social welfare rationale for the existence of multiple reserve requirements. We go on to present a model in which it is possible for a multiple reserves regime to improve social welfare relative to simpler regimes involving reserve requirements and/or deposit taxes. We demonstrate the empirical plausibility of our approach by providing a case study of Mexico, a country with extensive historical experience with multiple reserve requirements.
Keywords: 330; Finance; Public; Developing countries; Mexico; Bank reserves